Kewenangan Pemerintah Daerah Terhadap Penertiban Tanah Terlantar - Halirat, Novanda; Nendissa, Renny Heronia; Uktolseja, Novyta (Faculty of Law Universitas Pattimura, 2025)
Objects located on land above the surface of the earth have the right to regulate them. This is in accordance with the mandate of the provisions of Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Land can function well or have no right to use depending on how responsible the government and society are in managing the land. However, in reality there is a major polemic that arises regarding state land that is given to rights holders that are not used properly or are neglected for years. The purpose of this study is to determine and discuss the authority of the regional government in handling abandoned land and the form of legal protection for rights holders of abandoned land. The research method used in this writing is the normative legal research method with a statutory approach, case approach and conceptual approach, to answer the problems raised. The results of this study are that the Authority of the Regional Government in Handling Abandoned Land is carried out by the Head of the BPN Regional Office assigning the Head of the Land Control and Community Empowerment Division as the coordinator to prepare data and information regarding land indicated as abandoned (based on Article 8 paragraph (2) of the Regulation of the Head of the BPN RI No. 4 of 2010). For the implementation of data and information preparation activities in the field (land rights objects/basis for land control), the Head of the BPN Regional Office notifies the rights holders in writing that within a specified time, identification and research will be carried out until the stage of determining abandoned land. And the form of legal protection for rights holders of abandoned land is carried out both preventively and repressively. However, the most effective form of legal protection to be applied to this problem is the form of repressive legal protection on the grounds that there have been many violations of land abandonment in various regions in Maluku, one of which is Kandar Village. So that in order to strengthen land regulations, it is necessary to enforce repressive legal protection in the form of written warnings, administrative fines to pay compensation, revocation and transfer of land rights, and supervision of land control. With this, there is legal certainty that can be provided for the state, government and other communities who need land and their rights can be fulfilled based on the rule of law.